Modulation of cerebral cortex activity by acupuncture in patients with prolonged disorder of consciousness: An fNIRS study - Liu, Yiwei; Sun, Ning; Xiong, Jing; Zhou, Yuanfang; Ye, Xiangyin; Jiang, Hua; Guo, Hua; Zhi, Na; Lu, Jingkang; He, Peijue; Yang, Huilin; Li, Qingbin; et al. (Frontiers in Neuroscience, 2022)
Background and objective Acupuncture is a promising non-pharmacological therapy for patients with prolonged disorder of consciousness (PDOC); however, its underlying mechanism remains uncertain. This study aimed to reveal the modulatory effects of acupuncture on the cerebral cortex activity among patients with PDOC. Materials and methods Twenty-eight PDOC patients were randomly assigned to the treatment (n = 14) or control (n = 14) group. The treatment group received one session of acupuncture, while the control group received one session of sham acupuncture. All patients underwent evaluation of the functional connectivity and activation response of the dorsolateral prefrontal cortex (DLPFC), primary motor cortex (M1), and primary somatosensory cortex (S1) via functional near-infrared spectroscopy. We further explored the potential correlation of the consciousness level and activation response/functional connectivity with acupuncture. Results Compared to the control group, a single session of acupuncture significantly tended to enhance resting-state functional connectivity (rsFC) in DLPFC-M1, DLPFC-M1, and S1-S1. And the activation level of the DLPFC (both sides) in the acupuncture group is significantly higher than those in sham acupuncture group. However, no significant correlation was found between the consciousness level and activation response/functional connectivity. Conclusion One session of acupuncture has a significant modulation of rsFC and activation in the DLPFC, M1, and S1 with PDOC patients. Acupuncture-evoked effect may have some functional significance in PDOC patients. This is an important step toward exploring the acupuncture effects on PDOC patients.